Land access, land use, and agricultural practice: Political ecologies of servitude at colonial Ollantaytambo (1550–1770) - Raymond Alexander Hunter (Journal of Political Ecology)
Researchers have long noted connections between the creation of property in colonial contexts and environmental and ecological transformations. These links are most clear in settler colonial contexts, especially where property formation operated according to logics of 'improvement' that alienated Indigenous peoples from their lands and devalued traditional land use. In this article I present a case study from the Ollantaytambo region of Cusco, Peru to argue that property formation was also an ecological force in Spanish colonial contexts. I draw on political ecology theories of land access to suggest that the creation of the hacienda system of landholding instantiated an ecology of servitude predicated on unequal access to land and the organization of unfree labor. This colonial ecology structured land use and reshaped the local environment in enduring ways.